(3ebUhQI GHf OQjOs - (3GHf OQjO , CHh HcQ eMeO Hf GdMSf Hf OQjO GdCROj, GHf OQjO,J (B321 (3g` s
(3ChdgG (B:s
(3jG XHjI CTHg TF HGdegG QGJYI Hjf GdYbjb aGddhi s
(3BNQgG (B:s
(3Ch Cf CQi eNJVYkG dfcjI Ch dEHJgGL aQMkG Ch eROgi JeJ GdbUjOI GdebUhQI dGHf OQjO HMeO Gddg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B80 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B189 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B32s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1807s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3GdCOHs